Production objectives and management strategies of livestock keepers in south-east Kenya: Implications for a breeding programme - Hanotte, Olivier H.; Drucker, Adam G. (2005)
A survey of pastoralist and agropastoralist households in south-east Kenya was conducted to determine their production objectives and management strategies in order to optimize and extend a breeding programme for indigenous small East African Shorthorn Zebu cattle. The reasons for keeping cattle and the breed/trait preferences identified reflect the multiple objectives of the livestock keepers, with both adaptive traits and productive/reproductive traits rated as important. Although the Maasai and Kamba zebu (M&KZ) breeds were ranked highly with regard to adaptive traits, the population is considered to have been in decline over recent years. In order to promote the conservation and sustainable use of the M&KZ cattle, the formation of an open nucleus breeding scheme is recommended. In particular, such a scheme would be able to address several existing constraints (e.g. individual herds are very small and communal use of pastures/water makes controlled mating difficult). Such interventions would require the full participation of the livestock keepers, as well as ensuring that a holistic approach to species and breed attributes is taken into account in setting breeding goals, such that the full array of contributions that livestock make to livelihoods and the genetic characteristics related to these contributions are fully incorporated into the programme.